Energy Transition and The Impact of Biodiesel Development Policy on CPO Prices - Gultom, Gusti Artama; Harianto; Suharno (JEJAK, 2025)
Biodiesel is a renewable fuel with great potential to support energy transition in Indonesia. This research aims to analyze the impact of the policy of developing biodiesel on CPO prices. Time series and secondary data from January 2015 to December 2023 were used in this research with the Autoregressive Distributed Lag (ARDL) method. The dependent variable was the domestic CPO prices and the independent variable were the price of CPO in the international market, biodiesel production volume, exports of CPO and its processed products, price of palm cooking oil, export levies, export duties, CPO production volume, and the Rupiah exchange rate against the United States Dollar. The results in the short run was the domestic CPO prices were influenced positively and significantly by the volume of biodiesel production, the export volume of CPO and its processed products, and the price of palm cooking oil. In the long run, domestic CPO prices were significantly and positively influenced by international CPO prices and palm cooking oil prices. At the same time, export levy, CPO production volume, and the Rupiah exchange rate are significantly and negatively influenced. These results indicate that biodiesel production impacts the prices of biodiesel raw materials and cooking oil in the short run.